The high-tech CEO : how to lead R&D when you're not the expert - Rosier, Jan A. (Routledge, 2022)
"This book examines the impact of CEOs on firm performance and focuses on their role in science-based innovation to answer the question "Is it possible to lead highly complex R&D projects and innovation that you do not understand?" Today, science and technology move so fast that even managers of R&D teams can become quickly disconnected from new developments. Similarly, business leaders may be required to lead organisations with technical knowledge beyond their own expertise. How to manage teams and retain respect and influence is a recognised challenge. Filled with insight from managers and CEOs in science and technology organisations, the book unlocks the skills required to balance the leadership and managerial needs of the organisation, motivate the technical teams, and drive successful innovation in new product development environments. Due to the vital role played by experts in a chosen field of technical and scientific expertise, the book also describes what these specialists need and expect from their leaders. The book is required reading for managers in high tech and scientific environments - the CEO, CSO and the R&D manager. It can also be used as a classroom reference book on the management skills required for leading high-tech projects"--